Endemic Lake Baikal sponges from deep water. 2: Taxonomy and Bathymetric Distribution - Itskovich, Valeria B.; Kaluzhnaya, Oxana V.; Veynberg, Elena; Erpenbeck, Dirk (Zootaxa, 2017)
Unique samples of deep-water sponges of Lake Baikal were collected between 120 and 1450 m depth and their taxonomy and bathymetric distribution were studied. Based on morphological studies with scanning electron microscopy (SEM) and molecular analyses (CO1, ITS) we describe a new species, Baikalospongia abyssalis sp. nov. Spicule morphology of this new species is similar to Palaeoephydatia sp., a species previously known only from fossils in Late Pliocene (3.2−2.8 mya) sediments. Other sponge samples collected were identified as Baikalospongia intermedia intermedia, B. intermedia profundalis, B. bacillifera, B. fungiformis, B. martinsoni and Swartschewskia papyracea, all from the family Lubomirskiidae. Sponge specimens with giant spicules, identified as B. fungiformis, were found at great depths. B.i. intermedia and B. i. profundalis are dominating species at great depth. Light is a limiting factor for distribution of Lubomirskia baicalensis, possibly due to its symbiosis with photosynthetic protists. The current study extends our knowledge on the distribution boundaries of Lubomirskiidae at great depths.